Religion, language, and power - Green, Nile; Searle-Chatterjee, Mary (Routledge studies in religion, 2008)
Shows that the language of 'religion' is far from neutral, and that the packaging and naming of what English speakers call 'religious' groups or identities is imbued with the play of power.